Extracellular vesicle storm during the course of Ebola virus infection in primates - Vucetic, Andrea; Lafleur, Andrea; Côté, Marceline; Kobasa, Darwyn; Chan, Mable; Alvarez, Fernando; Piccirillo, Ciriaco; Dong, George; Olivier, Martin (Frontiers in Cellular and Infection Microbiology, 2023)
Ebola virus (EBOV) is an RNA virus of the Filoviridae family that is responsible for outbreaks of hemorrhagic fevers in primates with a lethality rate as high as 90%. It has previously been demonstrated that EBOV primarily targets host macrophages, and that this interaction leads to cell activation and systemic cytokine storm. Furthermore, fatal infection is associated with inhibition of interferon responses, suppression of dendritic cell function, and lymphopenia. However, the underlying mechanisms at play, along with the potential influence of other host-derived disease mediators such as extracellular vesicles (EVs), are either not well understood or limited to studies in epithelial cells. We sought to further elucidate the cellular and molecular events responsible for the EBOV-induced dysregulation of host immunity. To study the virus without BSL-4 containment, we generated EBOV virus-like particles (VLPs) expressing the viral glycoprotein (VLP-GP) and control VLPs without GP (Bald-VLP). Stimulation of human THP-1 monocyte-derived macrophages with VLPs showed induction of pro-inflammatory cytokine and chemokine gene expression that was exacerbated by the presence of GP. Cells collected from mouse peritoneal lavages six hours post-intraperitoneal challenge with PBS, VLP-GP, or Bald-VLP were analyzed by flow cytometry, revealing an increase in the recruitment of neutrophils and SPMs by all VLPs. In parallel, serum from two rhesus macaques infected with EBOV was assessed in a longitudinal study of the inflammatory events occurring during infection. Quantification of serum derived EVs isolated by size exclusion chromatography indicated that the concentration of vesicles peaked in circulation at the terminal stage of disease in the macaques. Comparative proteomics conducted across EV populations isolated from serum at various time points before and after infection revealed differences in both viral and host-derived protein content that were most pronounced at the endpoint of infection, including significant expression of viral GP and inflammatory mediators. These results suggest a dynamic role for EVs in the modification of disease states in the context of EBOV. Overall, our work highlights the importance of viral factors and host derived EVs in the inflammatory cascade and pathogenesis of EBOV, which can be collectively further exploited for novel antiviral development.